Clinical and radiological outcome of wide enbloc laminectomy with subaxial lateral mass screw fixation in patients of cervical spondylotic myelopathy with ossification of posterior longitudinal ligament: a prospective observational study - Chauhan, Lokendra Singh; Suthar, Lakshit; Shreyas, Cheemullu Shivashankar; Tak, Mahendra Singh (International Journal of Research in Orthopaedics, 2025)
Background: Data evaluating the clinical and radiological outcome of wide enbloc laminectomy with sub-axial lateral mass screw fixation in patients of cervical spondylotic myelopathy with ossification of posterior longitudinal ligament (OPLL) is scanty in the literature. Methods: This is a prospective observational study aimed to know the clinical and radiological outcome of wide enbloc cervical laminectomy with sub-axial lateral mass screw fixation in patients of cervical spondylotic myelopathy associated with OPLL. A total of sixty patients were included in our study who underwent wide enbloc cervical laminectomy and sub axial lateral mass screw fixation and were followed up to 1 year postoperatively. Modified Japanese orthopedic association (MJOA) score was used for functional outcome calculation, which was done at 1 month, 3 months, 6 months and 1 year postoperatively. We used C2-C7 Cobb’s angle as parameter of cervical alignment on lateral radiograph of cervical spine, modified Singh’s grading was used to asses cord compression on cervical spine MRI. Results: There was significant improvement in MJOA score from preoperative (12.2) to one year postoperative (15.7). The mean improvement in MJOA was 3.5 points. The average neurological recovery rate was 60.34%. Overall, 90% patients showed improvement in MJOA score. Cervical alignment is maintained from preoperative 15 degree to postoperative 14.3 degree. The average decrease in cobb’s angle was 0.7 degree and cord compression value improved from preoperative 2.7 to postoperative 0.4 according to modified Singh’s grade. Conclusions: Wide enbloc cervical laminectomy with sub-axial lateral mass screw fixation is a safe and effective treatment of multilevel cervical spondylotic myelopathy associated with OPLL providing a good functional outcome, maintaining adequate cervical alignment postoperatively.